Peran Kepala Madrasah Dalam Meningkatkan Keterampilan Mengajar Guru Fiqh Di MTs Al-Ikhlas Rantau Pulung - Moh. Tauhid; Eka Wahyuni; Akhmad Rifansyah; Ahmad Muhajir; Nur Muhammad Habibi (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2024)
The role of a madrasah head is very important in ensuring the effectiveness and success of educational institutions including improving the quality of the teachers he leads. The purpose of this study is to describe the role of the madrasah head in improving the teaching skills of fiqh teachers at MTs Al-Ikhlas Rantau Pulung, supporting factors and inhibiting factors in improving the teaching skills of fiqh teachers and solutions to deal with inhibiting factors in improving the teaching skills of fiqh teachers at MTs Al-Ikhlas Rantau Pulung. The method used in this research is a type of qualitative research then the approach used is a case study approach. To obtain the data and information needed in this study, researchers used interview, observation, and documentation techniques. The interviewees were two teachers at MTs Al-Ikhlas Rantau Pulung. The stages carried out by researchers in analyzing data are reducing data, namely summarizing and selecting the main things, after that the researcher presents the data in the form of a brief description using words or sentences to describe the data that has been obtained, then in the final stage the researcher draws conclusions from the data that has been obtained. The result of this study is the role of the madrasah head in improving the teaching skills of fiqh teachers at MTs Al-Ikhlas Rantau Pulung including by creating a conducive school environment, giving advice to teachers, providing motivation and encouragement to always seek as much information as possible, especially in terms of teaching skills. Supporting factors for the role of the madrasah head in improving the teaching skills of fiqh teachers with the willingness of teachers to continue to learn and seek information about basic skills in teaching, teacher creativity in developing material independently or adopting from experience and also from other book sources and good preparation prepared by teachers so as to facilitate the learning process. Meanwhile, the inhibiting factor is inadequate infrastructure.